A Clockwork Ear - Alicandri-Ciufelli, M.; Soloperto, Davide; Palma, Silvia; Marrara, Antonino; Genovese, Elisabetta (Neuropediatrics, 2012)
Objective tinnitus refers to a tinnitus that can also be heard by the examiner. It is a relatively rare condition, and can be misdiagnosed or neglected. Some causes of objective tinnitus are head and neck vascular malformations, or muscular myoclonus of the tensor tympani, stapedial, or palatal muscles. The case of an 11-year-old girl with an objective tinnitus lasting from 1 year is herein presented, and the diagnostic workup performed in this unusual case is described.
Keywords: objective tinnitus; palatal myoclonus; botulinum neurotoxin; inferior olive; audiometric evaluation